1993
DOI: 10.1091/mbc.4.10.1003
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast genes nda1+ and nda4+, mutations of which lead to S-phase block, chromatin alteration and Ca2+ suppression, are members of the CDC46/MCM2 family.

Abstract: Fission yeast cold-sensitive mutants ndal-376 and nda4-108 display a cell cycle block phenotype at the restrictive temperature (cell elongation with the single nucleus) accompanied by an alteration in the nuclear chromatin region. DNA content analysis shows that the onset of DNA synthesis is blocked or greatly delayed in both mutant cells, the block being reversible in nda4-108. Upon release to the permissive temperature, nda4-108 cells resumed replicating DNA, followed by mitosis and cytokinesis. The nda4 phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…It was observed that a cold-sensitive mutation of Mcm5, nda4-108 (Miyake et al 1993), suppressed the HU sensitivity of mrc1D as well as cds1D cells at 35°( Figure 7C). It was confirmed that the nda4 mutation is a bona fide cause of the suppression in mrc1D cells, by comparison of the HU sensitivity of nda4 mrc1D transformants harboring an empty vector or the plasmid containing the nda4 1 gene (p.vector and p.nda4, respectively) ( Figure 7D).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was observed that a cold-sensitive mutation of Mcm5, nda4-108 (Miyake et al 1993), suppressed the HU sensitivity of mrc1D as well as cds1D cells at 35°( Figure 7C). It was confirmed that the nda4 mutation is a bona fide cause of the suppression in mrc1D cells, by comparison of the HU sensitivity of nda4 mrc1D transformants harboring an empty vector or the plasmid containing the nda4 1 gene (p.vector and p.nda4, respectively) ( Figure 7D).…”
Section: Resultsmentioning
confidence: 93%
“…However, a cold-sensitive mutation of Mcm2, nda1-367 (Miyake et al 1993), suppressed the HU sensitivity of cds1D but not mrc1D cells at 33°( Figure 7B). These Figure 4.-Suppression of the HU sensitivity of the replication checkpoint mutants by the orp1-4 or the sna41-928 mutation.…”
Section: Resultsmentioning
confidence: 96%
“…mMCM2, which consisted of 904 amino acids, had 87.1, 47.4 and 44.4% identity with the human, S. pombe and S. cerevisiae homologues at the amino acid level and also showed conservation of the CX 2 CX 19 CX 2 C-type zinc finger-like motif ( Fig. 2) (Yan et al 1991;Miyake et al 1993Miyake et al , 1996Todorov et al 1994). mMis5 consisted of 868 amino acids, had 46.1, 54.9 and 95.3% identity with S. pombe, C. elegans and rat homologues (Takahashi et al 1994;Sykes & Weiser 1996) and also contained the CX 2 CX 19 CX 4 C-type motif as observed in mCdc21 and mCDC47 ( Fig.…”
Section: Sequence Of Mmcm2 and Mmis5 Proteinsmentioning
confidence: 99%
“…The Mcm gene family is conserved from yeast (3,4,(7)(8)(9)(10)(11) to mammals (12)(13)(14)(15) and consists of at least six members (Table 1). All genes examined in yeasts are essential for cell growth and their mutation causes cell cycle arrest in S phase (3,4,(6)(7)(8)(9)(10)16).…”
Section: Introductionmentioning
confidence: 99%
“…All genes examined in yeasts are essential for cell growth and their mutation causes cell cycle arrest in S phase (3,4,(6)(7)(8)(9)(10)16). In mammalian cells, DNA replication is inhibited when antibody against human MCM2 homolog, BM28 (14) or mouse P1MCM3 (15) is microinjected into the nucleus.…”
Section: Introductionmentioning
confidence: 99%